Penerapan Pola Arsitektur Model-View-ViewModel pada Aplikasi Pembelajaran Shorof Berbasis Mobile - Havidz Muhammad Iqbal; Oddy Virgantara Putra; Dihin Muriyatmoko (Ikatan Ahli Informatika Indonesia, 2024)
This research aims to develop an Android-based Basic Shorof learning application using Model-View-ViewModel (MVVM) architecture pattern. The background of this research focuses on the difficulties faced by Non KMI students at Darussalam Gontor University in understanding Shorof material, which is a major challenge in Arabic language learning. Many students have difficulty in understanding the basic concepts of Shorof, which is an important component in the overall mastery of the Arabic language. This research method includes data collection through questionnaires distributed to students. The purpose of this data collection was to identify the difficulties faced by students in learning Shorof. Analysis of the questionnaires showed that many students have difficulties in understanding the basic concepts of Shorof. This finding became the basis for the development of a learning application that is easy for students to use. The developed application uses MVVM approach to separate the business logic from the user interface. This approach facilitates future development, testing, and maintenance of the application. The features of this application include learning modules, quizzes, and Arabic vocabulary designed to strengthen students' understanding of Shorof material. Application testing involved a number of students as respondents to measure the effectiveness and efficiency of the application in improving their understanding of Shorof material. The test results showed that students experienced an increase in understanding after using this application. In conclusion, the application of MVVM architecture pattern in the development of Basic Shorof learning application can improve students' understanding effectively. This research is expected to have a positive impact on the development of educational applications in the future. Thus, this application is useful not only for students of Darussalam Gontor University, but also for the development of Arabic learning methods more broadly in various educational institutions.